Effectiveness of digital game-based learning in enhancing primary four pupils’ achievement in fraction / Boo Jia Yi - Boo , Jia Yi (2020)
Fraction is one of the basic concepts in Mathematics but the general understanding of the concept is still inadequate among pupils in elementary schools. A hindrance in the method of teaching and the lack of technological tools in the topic of fraction have led to the need of a deeper understanding about the causes of low achievement among Malaysian pupils in Mathematics. This study aims to examine the effectiveness of a digital game-based learning in enhancing Primary Year Four Pupils’ achievement in fraction. A quasi-experimental research design was conducted to answer the three research questions of this study. The sample of this study consists of 56 pupils Year Four primary pupils from two equal sizes of intact classes in one of the Chinese primary schools (SJKC) in Kuala Lumpur. They participated in this study with one class assigned as the control group (N= 28) and the other as an experimental group (N = 28). The experimental group was taught using the Zapzapmath app as digital game-based learning which is designed based on cognitive information processing theory and Gagne’s conditional theory. The intervention for the experimental group was conducted for six weeks. The control group was taught using the traditional approach. Pre and Post Fraction Achievement Test were administered to pupils in both the experimental group and the control groups before and after the intervention. Inferential statistics such as Wilcoxon signed-rank test and Mann-Whitney U test were used in analyzing the quantitative data obtained. Results of Wilcoxon signed-rank test indicated that there were no significant difference between the means of the pre-test and post-test of the pupils in control group, when z = -1.04, p = 0.30. After six weeks of intervention, the results of the Wilcoxon signed-rank test had shown that there was a significant difference between the means of the pre-test and post-test of the pupils in experimental group (z = -4.56, p ‹ .001). This means that pupils in the experimental group have improved significantly in post-test as compared to the pre-test after the digital game-based learning approach. Furthermore, results of the Mann-Whitney U test revealed that the post-test for the experimental group and control group were statistically significantly different, U (